An experience of using Rivaroxaban (Xarelto®) in the treatment of lower extremity fractures - Palamarchuk, Vladislav; Bulavin, Konstantin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article contains an analysis of the results of prevention of venous thrombembolism (up to 35 days) in patients with fractures of their femoral and tibial bones, who were subjected to osteosynthesis. Two groups of patients were compared: the 1st was recommended to take Clexane, the 2nd one took Rivaroxaban (Xarelto(R)). In outpatient conditions, the prevention of venous thrombembolism lasted in 12.5 % of patients from the 1st group, and in 70.8 % from the 2nd one.